Analisis Framing Headline Tentang Wacana Kenaikan Harga BBM Di Harian KOMPAS dan SOLOPOS Periode Maret 2012 - Herawati, Aprillia; Maharani Serikit, Poundra Swasty Ratu (KOMUNITAS, 2013)
Background of the research is authorâs interest with issue of increased price of fuel oil in which it became a popular discussion among people when the issue was starting to develop. The issue of fuel oil price upsurge running about March2012. The research uses framing analysis method by using Zhongdan Pan and Gerald M. KosickiÂ  instruments. The headlines of Kompas and Solopos newspapers are then analyzed by using framing tool from Pan Konsicki consisting of four big structures, namely, syntax, script, thematic, and rhetoric.Â  Findings of the research indicated that Kompas and Solopos newspaper have different frames about phenomenon of fuel oilÂ  priceÂ  upsurge.Â  TheÂ  differentÂ  framesÂ  usedÂ  byÂ  KompasÂ  andÂ  Solopos newspapersÂ  inÂ  framing newsÂ  ofÂ  theÂ  phenomenonÂ  discourseÂ  wereÂ  inÂ  syntaxÂ  aspect;Â  especiallyÂ  thoseÂ  wereÂ  relatedÂ  with headline and informant.